‘Wasn't me!’: a field study of the relationship between deceptive motivations and psychopathic traits in young offenders - Spidel, Alicia (Legal and criminological psychology, 2011)
Purpose. Evaluating truthfulness is an integral part of any forensic assessment. Unfortunately, the motives underlying the use of deceptive strategies by offenders and how these may be mediated by personality are not well established, particularly in adolescent samples. Accordingly, the aim of the present study was to identify different deception-related motivations in a sample of juvenile offenders, with special emphasis placed on the relationship between these motivations and psychopathic traits. Methods. Archived file and videotaped information for 60 Canadian federal juvenile offenders were reviewed in order to identify real-life (spontaneous) patterns of deceptive motivations. Results. It was found that there were significant differences between the low, medium, and high groups across psychopathic traits for the motivations of (1) lies to obtain a reward; (2) to heighten self-presentation; and (3) for duping delight. Conclusions. Not only were juvenile offenders found to lie for a variety of reasons, but also psychopathy was found to mediate the specific motivational patterns leading to offender perpetrated deception. The relevance of these findings to the assessment of truthfulness in offender populations is discussed.